Foot structure in collegiate tennis players shows side-to-side difference - Shinozuka, N.; Torii, S.; Okumura, K. (Medicine and Science in Tennis, 2009)
Background: Tennis is a typical sport with asymmetric motion of both extremities. Athletes participating in asymmetric sports show side-to-side difference (SSD) in strength, muscle volume, and injury occurrence in their extremities. There are many studies about SSD of arm in tennis and baseball players. But few studies were conducted about SSD of foot structure. Purpose: To determine foot structure SSD in collegiate tennis players. Methods: We measured foot length (FL), foot width (FW), and navicular height (NH) at standing (weight bearing) and at sitting (non-weight bearing) position for 55 collegiate right-handed tennis players (TN group) and 12 long distance runners (LD group). Also, we measured leg-heel angle (LHA) at standing. Arch height ratio (AHR) was calculated, dividing NH by FL. We administered paired t-test to determine the SSD of each parameter, and Pearson correlation analysis between LHA and NH or AHR. Significance for statistical test was set at P less than 0.05. Results: In TN group, NH and AHR were significantly higher in right foot than in left foot, and FW was significantly larger in right foot than in left foot. LHA was significantly larger in left foot than in right foot. In LD group, NH and AHR were significantly higher in right foot than in left foot. Discussion: In this study, we hypothesized that athletes of asymmetric sport showed SSD in foot structure. Our results confirmed the hypothesis for TN group, although we could not identify which of the athletic motion results in SSD of the foot. Understanding specific laterality of the feet in TN group will give important information to build reconditioning plan and training menu for athletes with lower extremity injuries, such as shin splint and plantar fasciitis.